Bydgostiana w zbiorze rękopisów Wojewódzkiej i Miejskiej Biblioteki Publicznej w Bydgoszczy (Kronika Bydgoska, 2013)
The Voivodeship and Municipal Public Library in Bydgoszcz has gathered a huge stock of Bydgostiana. They can be seen at the Regional Room, which collects books and magazines, and in the Special Collections Department, which stores old prints, manuscripts, maps, iconography, musicalia, and social life documents. Particularly valuable is the collection of manuscripts including unique manuscripts and mostly concerning Bydgoszcz and its vicinity. The archives include administration documents, sources from the scope of judiciary, economy, education, literature, culture, as well as religious, urbanization, political and social issues. These manuscripts date back first of all to the 18th-20th centuries, and they were written mainly in Polish and German. They amount to 1,201 inventory units, including both individual documents and comprehensive collections of files.